Analisis Putusan Nomor 286 K/TUN/2017 Sebagai Keputusan Fiktif Negatif Ditinjau Dari Asas Pemerintahan Yang Baik - Lailil Maghfiroh; Aqila Hafiya (Universitas Kapuas, 2024)
Negative fictitious decisions are caused by state administrative bodies or officials remaining silent on decisions that should be issued. In this journal, the author wants to explore and analyze negative fictitious decisions from a dispute over granting a plantation business permit. The author uses a library study research method, which collects information from various sources, such as books and journals. The conclusion that the author can find from this article is that it is true that decision number 286 K/TUN/2017 is an example of a negative fictitious decision, this is because the defendant, in this case, the Regent of Kutai Kartanegara, did not give an answer to the plaintiff or remained silent.